Self-regeneration of a Ni–Cu alloy catalyst during a three-way catalytic reaction. Issue 35 (12th June 2019) - Asakura, Hiroyuki; Onuki, Tetsuo; Hosokawa, Saburo; Takagi, Nozomi; Sakaki, Shigeyoshi; Teramura, Kentaro; Tanaka, Tsunehiro
Abstract : Ni–Cu alloy supported on γ-Al2 2O3 catalysts exhibit high catalytic activity and durability for a three-way catalytic reaction under both oxidative and reductive conditions because of their self-regenerating feature. Abstract : Ni–Cu alloy supported on γ-Al2 O3 catalysts prepared by high-temperature hydrogen reduction exhibit high catalytic activity and durability for a three-way catalytic reaction under both oxidative and reductive conditions because of their self-regenerating feature. DFT calculations showed that Ni-oxide was reduced to Ni metal by CO in the presence of Cu metal because of the Ni–Cu alloy effect but was not in the absence of Cu metal.